Restorative Justice In Adult Women Victims Of Electronic-Based Sexual Violence - Irawan, Joshua; Mugiono, Mariana; Angjaya, Vanessa Ileana; Permatasari, Dewi Shinta (Journal of Law and Policy Transformation, 2024)
Sexual Violence is a form of criminal act that in the modern era is very common in Indonesian society. Based on data from the KOMNAS Perempuan RI, in 2021 there have been approximately 1,721 Reports cases of violence against women. This Sexual Violence does not only occur physically, but has evolved into Electronic-based Sexual Violence. This Electronic-Based Sexual Violence has been regulated based on Article 14 paragraph (1) TPKS Law. The resolution of Sexual Violence Criminal Acts cases has so far been carried out on a criminal basis, which does not pay attention to the interests of victims. Therefore, the Writing Team tries to use Restorative Justice (RJ) as one way or alternative to solve cases of Sexual Violence Crimes, especially for electronic-based sexual violence in order to pay more attention to the rights of victims. This paper is written with the Dogmatic Normative Juridical research method which is realized through a conceptual approach and statute approach. The final result of this study is that RJ can still be applied both at the level of investigation and prosecution of electronic-based sexual violence crimes with notes: The article imposed on the perpetrator is Article 14 paragraph (1) of the TPKS Law where the threat of imprisonment is 4 years; there is no rejection from the Society ; there is peace between the perpetrator and the victim ; and the rights of victims are restored again by redress or other exercise of responsibility of the perpetrator. If one condition is not met, then RJ cannot be carried out and the criminal justice process continues in accordance with the Indonesian criminal procedure law.